Applicability of an HPLC method for analysis of alcoholic and glycolic Brazilian green-propolis extracts - Camila Felix Vecchi; Rafaela Said dos Santos; Marcos Luciano Bruschi (Universidade de São Paulo, 2023)
Abstract Brazilian green propolis has been widely used in food and pharmaceutical products due to its valuable source of phenolic compounds and versatile biological activities. The development and validation of analytical methods are extremely useful for the characterization and quality control of products containing propolis. Therefore, the aim of this study was to optimize, validate and investigate the applicability of a reversed-phase HPLC method for analysis of different types of Brazilian green propolis extracts (glycolic and ethanolic). The method showed to be selective for the propolis phenolic markers. The analysis of variance and residues demonstrated that the method had significant linear regression, without lack of fit. It was also a precise, accurate and robust method, which was of utmost importance to analyze both glycolic and ethanolic extracts and at different concentrations. Moreover, as these products can display most complex matrices to analyze, a valid HPLC method can also prove to be specific and versatile.